We the peoples. Millennium report. The role of the United Nations in the 21st century - General de las Naciones Unidas, Secretario (2016)
The new millennium, and the Millennium Summit, offer the peoples of the world a unique opportunity to reflect on their common destiny at a time when they are more interrelated than they have ever been. The people expect their leaders to point out the challenges of the future and take measures to face them. The United Nations can help meet these challenges if its Members agree to reorient the mission they must fulfill. The United Nations, which was founded in 1945 to introduce new principles in international relations, has achieved better results in some areas than in others. This is an opportunity to restructure the United Nations so that they can really contribute to improving the lives of peoples in the new century.